A GIS based water end-use demand modeling - Gato, Shirley (Philippine computing journal)
The end use of water is a breakdown of the total household water usage such as water used for toilets, showers, washing machines, taps, lawn watering, etc. The Victorian government, is Australia set a 15% per capita consumption reduction target by 2010 based on the Water Resources Strategy that has been developed for Melbourne. Therefore, there is a need to measure and model residential end uses of water to ensure the effectiveness of conservation efforts and to determine whether the set target reduction is achieved. This paper describes GIS-based modelling of end uses of water from a number of single-family homes in Greater Melbourne, Australia. The study involves the analysis of water demand data at 1-minute and 5-second intervals from logged households collected by Yarra Valley Water in Melbourne, Australia in 2001 and 2004. The result of this study improves understanding on the end uses of water and provides information to assist where to focus water conservation efforts that would yield the most effective result financially, environmentally and acceptable to everyone.